CHEMICAL CONTROLS ON THE DISTRIBUTION OF CRITICAL METALS IN THE HACKETT RIVER ZN-PB-CU-AG MAIN ZONE VOLCANOGENIC MASSIVE SULFIDE DEPOSIT, NUNAVUT - Keane, Siobhan Tara (2025)
The 2.68 Ga Zn-Pb-Cu-Ag Hackett River Main Zone volcanogenic massive sulfide (VMS) deposit is in the Hackett River Greenstone Belt (Nunavut), part of the Slave Craton. VMS deposits are polymetallic and host a variety of critical metals. Samples from a drill hole that stratigraphically transects the mineralization were studied. Within this hole, copper is enriched in the footwall, and this decreases in abundance higher in the mineralized lens; this is followed upward by enrichment in Zn, and finally Pb enrichment towards the top of the mineralized lens. “Ore” minerals present are: chalcopyrite, galena, pyrite, pyrrhotite, sphalerite, and tetrahedrite. Samples were analyzed for bulk geochemistry, and mineralogy and mineral chemistry by SEM-MLA and LA-ICP-MS. The residence, zonation, and deportment of fifteen critical metals (Mn, Mn, Cd, Co, Ni, As, Sb, Ag, Bi, Se, Sn, In, Ga, Ge, Mo, Tl) were determined. Towards the stratigraphic top of the mineralized lens Ag (and Sn) is resident in tetrahedrite and galena. Galena is the dominant host for these elements where tetrahedrite is not present (i.e., not precipitated), suggesting that both elements are controlled by temperature of the mineralizing fluid. Cadmium, Mn, and Ga reside in sphalerite. Manganese2+ and Cd2+ substitute for Zn2+ in the sphalerite crystal structure. Similarly, Ga2+ substitutes for Zn2+ and there is element competition between Ga and Zn for space in the sphalerite crystal lattice. Bismuth and Tl occur as substitutions for Pb due to “incremental” crystallization from a circulating hydrothermal fluid, wherein the “reservoir” of these elements is quickly depleted once galena starts to precipitate. The highest Co concentrations in pyrite are toward the middle of the mineralized lens and the highest Ni concentrations occur toward the top of the mineralized lens. Both Co2+ and Ni2+ substitute for Fe2+ in the pyrite crystal structure. The difference in their enrichment through the mineralized lens indicates that the elements are in competition with each ...